(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The purpose of this study is to investigate the nutritional, economic, and microbial properties of Haematostaphis barteri (zimberima), an underutilised indigenous fruit in Ghana’s Upper West Region, and to evaluate its potential as a raw material for wine production. Design/Methodology/Approach: Ripe Haematostaphis barteri fruits were harvested in 2023 and processed to extract juice, which was fermented to produce “Jimb Wine”. Proximate and mineral compositions were analysed using standard Association of Official Analytical Chemists (AOAC) methods. A microbial test was conducted to assess the presence of Enterobacteriaceae, yeast, and mould to ensure safety. The alcohol and Vitamin C contents were also measured to determine the wine’s nutritional value. The data were subjected to analysis of variance (ANOVA). The statistical package used was the Student Edition of Statistix 9.0 Research Limitation: The study was conducted within a single harvest season and a specific geographic location within Ghana’s Upper West Region, which may not capture variations in fruit composition due to climate, soil, or seasonal changes. Consumer sensory evaluation and long-term storage stability were not assessed. Findings: Haematostaphis barteri wine (Jimb Wine) possesses high nutritional value, with carbohydrate, fibre, and protein contents of 59.4%, 12.05%, and 8.8%, respectively. Mineral analysis revealed significant levels of potassium (970.81 mg/l), calcium (192.08 mg/l), and phosphorus (111.49 mg/l), which contribute to the wine’s flavour and stability. Microbial testing confirmed the absence of Enterobacteriaceae, indicating product safety, while the presence of yeast and mould supported its natural fermentation potential. The final wine contained 9.46% alcohol and retained 78% of its original Vitamin C, highlighting its potential as a nutritious, locally made beverage. Practical Implication: Haematostaphis barteri can be effectively used to produce a safe, nutritious, and marketable fruit wine, offering a viable opportunity for food diversification and value addition. Social Implication: Promoting this indigenous fruit supports rural innovation, encourages sustainable use of local resources, and helps combat poverty through income diversification. Originality/Value: It highlights the underexplored value of an indigenous fruit traditionally used by the Dagaba people. The findings provide a foundation for further research, commercialisation, and policy support to promote indigenous crops for sustainable livelihoods and food security.